Pengaruh Media Power Point Interaktif terhadap Hasil Belajar Siswa pada Tema 7 Subtema 1 Kelas IV SD Negeri Percontohan Kabanjahe T.A. 2022/2023 - Riska Uli Enjelina Br Sidabariba; Nurmayani Nurmayani; Ibrahim Gultom; Lidia Simanihuruk; Dodi M. Pandimun Ambarita (FKIP, Universitas Palangka Raya, 2024)
The problem in this study is the low learning outcomes of fourth grade students at SD Negeri Percontohan Kabanjahe T.A. 2022/2023. The purpose of this study was to determine the effect of Interactive Power Point Learning Media on Student Learning Outcomes in Theme 7 Sub-theme 1 Class IV SD Negeri Pilot Kabanjahe T.A. 2022/2023. The research used is a quantitative research, with a quasi-experimental design research type using the Pretest-Posttest Nonequivalent Control Group Design. The population in this study were all students of class IV SD consisting of 30 students in class IV-A and 28 students in class IV-B. The research sample uses the Total Sampling technique, which means using the entire existing population. The data collection instrument used in this study was a test instrument. The results showed that the average value of learning outcomes using interactive power point media was 78.33, while the average value of learning outcomes using poster media was 71.25. The results of hypothesis calculations using the t test, the results obtained were t_count > t_table, namely 3.160 > 1.673 then Ha is accepted and H0 is rejected. So, it can be concluded that there is a significant positive influence between interactive power point learning media on student learning outcomes.